2019
DOI: 10.3390/en12173395
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on EMI Mitigation Techniques: Intent to Reduce Grid-Tied PV Inverter Common Mode Current and Voltage

Abstract: Power inverters produce common mode voltage (CMV) and common mode current (CMC) which cause high-frequency electromagnetic interference (EMI) noise, leakage currents in electrical drives application and grid-connected systems, which consequently drops the efficiency of the system considerably. This CMV can be mitigated by designing suitable EMI filters and/or investigating the effects of different modulation strategies. In this paper, the effect of various modulation techniques over CMV and CMC are investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The CE causes significant electrical damages and communication malfunctions in many systems [17][18][19][20][21][22][23][24]. To reduce the CE, there are several methods [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] with different signal attenuation patterns. Each electrical system has different CE characteristics, so the CE attenuation method must be appropriately chosen for each system.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The CE causes significant electrical damages and communication malfunctions in many systems [17][18][19][20][21][22][23][24]. To reduce the CE, there are several methods [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] with different signal attenuation patterns. Each electrical system has different CE characteristics, so the CE attenuation method must be appropriately chosen for each system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…CM and DM were analyzed and discussed in detail to design the EMI filter. The research of Subramaniam et al [31] presented the CM reduction in the three-phases grid-tie inverter. The result showed that the harmonic injection method reduced CMV and CMC by 60%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nowadays, renewable energy sources play a key role in supporting the power system to adapt the ever-increasing load demand. Among the renewable energy sources, the PV source is considered as one of the most effective solutions due to its relatively small size, clean energy, noiseless operation, and simple installation [1][2][3][4]. To connect the PV array with a utility grid, grid-connected inverters are widely used for the PV systems and are divided into the transformer-based and transformerless topologies [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Among the renewable energy sources, the PV source is considered as one of the most effective solutions due to its relatively small size, clean energy, noiseless operation, and simple installation [1][2][3][4]. To connect the PV array with a utility grid, grid-connected inverters are widely used for the PV systems and are divided into the transformer-based and transformerless topologies [4][5][6][7][8][9]. The use of a high-frequency transformer on the DC side or a low-frequency, bulky transformer in the AC side can be employed to ensure the safety issue with the galvanic isolation between the output and input sides [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in case the centralized rectifier fails, the common DC-bus can be powered by battery connected to the DC-link system which can provide sufficient power to continue the load system at the same operating conditions (in the meantime it is possible to do maintenance of the rectifier system). Additionally, it is possible to connect renewable energy resources such as PV inverters due to their DC nature with ease at the common DC-bus of the multidrive system [10,11] and [7,12], [J2] shown in Fig. 1.3. Despite the above stated benefits, one of the main challenges of the multidrive system is the presence high DC-link current harmonics content in the system [13][14][15] which may cause failure of fragile components such as DC-link capacitors [2,16].…”
Section: Common Parallel Connected Multidrive Systemmentioning
confidence: 99%